Tackling the urban heat islands phenomenon: development of coaxial fibers with phase change materials - Hammes, Nathalia (2024)
Urban heat islands (UHI) represent a growing challenge due to the current world’s global warming trend affecting the health and quality of life of citizens. Furthermore, UHI does add up to climate change and undermine environmental sustainability in a rather negative way. The population, in general, and in particular our students and youngsters, should be aware of this problem and of the possible solutions that are in development aiming the mitigation of this effect. In this chapter, we will briefly present a research work developed at the University of Minho, with the participation of the Federal Institute Goiano, in the development of advanced materials with thermoregulation properties to be incorporated in road pavements and building construction materials. This study investigates the development of coaxial fibers composed of phase change materials (PCMs) to be used in building materials as thermoregulation agents under the latent heat principle. Co-axial phase change fibers (PCFs) were developed, with cellulose acetate (CA) as the sheath and polyethylene glycol (PEG) as the core, using the wet-spinning technique. The analyses confirmed a sheathcore morphology and thermal capacity of PCFs. These innovative materials offer a practical approach to mitigating thermal impact in urban environments.